Day 1 Tue, February 04, 2020 2020
DOI: 10.2118/199718-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Imaging of Perforation Erosion in Hydraulically Fractured Wells for Optimizing Cluster Efficiency

Abstract: A new solid-state, high-resolution acoustic imaging technology has been applied in hydraulically fractured wells to image and quantify perforation erosion. The downhole device captures detailed full-lateral logs of horizontal wells, without the need for clear fluids to facilitate measurements. This paper discusses how the imaging technology functions, lab testing that validated the measurements, and field testing completed with several operators in a variety of reservoirs and basins. This high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A more detailed version with examples can be found in [29]. The workflow for optimizing perforation design employs StageOpt simulator and observation of field-scale phenomena, such as downhole imaging that provides costeffective and high-fidelity assessment of the magnitude and location of perforation erosion within a stage [26,30]. The data can include the equivalent diameter, as well as axial and circumferential diameters.…”
Section: History Matching Workflow With Stageoptmentioning
confidence: 99%
“…A more detailed version with examples can be found in [29]. The workflow for optimizing perforation design employs StageOpt simulator and observation of field-scale phenomena, such as downhole imaging that provides costeffective and high-fidelity assessment of the magnitude and location of perforation erosion within a stage [26,30]. The data can include the equivalent diameter, as well as axial and circumferential diameters.…”
Section: History Matching Workflow With Stageoptmentioning
confidence: 99%
“…A Midland basin case was reported by Murphree et al (2020) where unexpected casing breaches were observed at 16% of the frac plug set depths. An abundance of downhole acoustic images was provided to demonstrate the correlation between casing erosion and frac plug location (Robinson et al 2020).…”
Section: Current Industry Observationmentioning
confidence: 99%
“…So as to improve the effectiveness of fracturing operation. S robinson [8] used the acoustic system to evaluate the hole erosion in the perforated section of a horizontal well. After quantifying the collected data, the hole diameter, hole erosion range, hole erosion offset and other information are obtained.…”
Section: Introductionmentioning
confidence: 99%